2014
DOI: 10.3390/atmos5040788
|View full text |Cite
|
Sign up to set email alerts
|

Neural Fuzzy Inference System-Based Weather Prediction Model and Its Precipitation Predicting Experiment

Abstract: Abstract:We propose a weather prediction model in this article based on neural network and fuzzy inference system (NFIS-WPM), and then apply it to predict daily fuzzy precipitation given meteorological premises for testing. The model consists of two parts: the first part is the "fuzzy rule-based neural network", which simulates sequential relations among fuzzy sets using artificial neural network; and the second part is the "neural fuzzy inference system", which is based on the first part, but could learn new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…After development of ANN based model Krishna, [44], Malik et al, [52], have found that the world's most population, specially the country like India, are depend on the cultivation, where the livelihood of the people are mostly dependent on the monsoon. Further, Baboo and Shereef, [8], Jillella S.S. et al, [35], have also observed that the impact of the monsoon on the livelihood of the Indian families, for prediction of the monsoon rainfall they have applied the Neural Networks package which supports different types of training or learning algorithms on which most useful algorithm is Back Propagation Neural Network (BPN) technique. They have applied Curve fitting and Extrapolation methods with back propagation and found that used model is the most important for prediction of weather.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After development of ANN based model Krishna, [44], Malik et al, [52], have found that the world's most population, specially the country like India, are depend on the cultivation, where the livelihood of the people are mostly dependent on the monsoon. Further, Baboo and Shereef, [8], Jillella S.S. et al, [35], have also observed that the impact of the monsoon on the livelihood of the Indian families, for prediction of the monsoon rainfall they have applied the Neural Networks package which supports different types of training or learning algorithms on which most useful algorithm is Back Propagation Neural Network (BPN) technique. They have applied Curve fitting and Extrapolation methods with back propagation and found that used model is the most important for prediction of weather.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What distinguishes the weather and climate prediction is the span of time and the type of element that is forecasted [6]. Weather predictions mention almost all the elements of weather, climate predictions over ranges while the amount of rainfall and the beginning of the season.…”
Section: Bmentioning
confidence: 99%
“…The most widely-used technique for weather forecasting is linear or least squares regression [24]. Lu et al [25] presented a weather predicting system based on a neural network and fuzzy inference system, which is out of scope of the current work. TITAN assumes the decay and growth of storms follow a linear trend, while storm motion occurs along a straight line.…”
Section: State-of-the-artmentioning
confidence: 99%